2014
DOI: 10.1056/nejmoa1304923
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Immunogenicity of an Enterovirus 71 Vaccine in China

Abstract: The EV71 vaccine provided protection against EV71-associated hand, foot, and mouth disease or herpangina in infants and young children. (Funded by Sinovac Biotech; ClinicalTrials.gov number, NCT01507857.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
296
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 398 publications
(312 citation statements)
references
References 24 publications
5
296
2
1
Order By: Relevance
“…Three biological product companies have completed the phase III clinical trial of EV71 inactivated vaccine and the results show that the vaccine is safe and effective. 23,32,33 Our findings suggest that more financial resources should be invested toward the prevention and management of EV71-associated disease, especially the severe HFMD. The department of health administration and government should reduce the disease burden of patients through various measures such as improving medical cost reimbursement, optimizing methods for diagnosis or treatment of EV71-associated disease.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Three biological product companies have completed the phase III clinical trial of EV71 inactivated vaccine and the results show that the vaccine is safe and effective. 23,32,33 Our findings suggest that more financial resources should be invested toward the prevention and management of EV71-associated disease, especially the severe HFMD. The department of health administration and government should reduce the disease burden of patients through various measures such as improving medical cost reimbursement, optimizing methods for diagnosis or treatment of EV71-associated disease.…”
Section: Discussionmentioning
confidence: 86%
“…23,33 The surveillance and definition of EV71-associated disease was referred to in these trials. We investigated 343 cases due to EV71 infection, which were reported between 2011 and 2013 by the Ganyu and Sheyang prefecture Centers for Disease Control and Prevention.…”
Section: Methodsmentioning
confidence: 99%
“…However efforts have been initiated to develop a vaccine against specific EVs most notably EV-71 (Liang and Wang, 2014;Lu, 2014;Zhu et al, 2014). …”
Section: Poliomyelitis Vaccination and Eradication Updatementioning
confidence: 99%
“…8,9 Currently, 3 inactivated EV71 vaccines developed in China have demonstrated good efficacy and safety profile in the phase 3 clinical trials. [10][11][12] These 3 EV71 vaccines are very likely to be the first available vaccines against EV71-associated disease in the world.…”
Section: Introductionmentioning
confidence: 99%
“…In two of the 3 trials, 10,12 correlate of immunity againstEV71-associated disease was explored by applying a receiver operating characteristics (ROC) curve analysis in a subset of cohort selected by matching each case with 5 controls. The results suggested that antibody titers of 1:16-1:32 with the maximum Youden index might be a possible serologic marker for protection against EV71-associated disease.…”
Section: Introductionmentioning
confidence: 99%